The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.3176/earth.2008.4.02
|View full text |Cite
|
Sign up to set email alerts
|

Karksilepisparva gen. et sp. nov. (Chondrichthyes) from the Burtnieki Regional Stage, Middle Devonian of Estonia

Abstract: Dermal scales of a new chondrichthyan were discovered in four levels in sandstones of the Härma Beds (lower part of the Burtnieki Regional Stage, Middle Devonian) in the Karksi outcrop of South Estonia. The classification of Karksilepis parva gen. et sp. nov. Märss is still uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…As in Scotland (Figure 2.2), D. crassisimus has quite a long range in the eastern Baltic, also found in the Eifelian Narva Formation (Valiukevičius 1985(Valiukevičius , 2003. Märss et al (2008) also report D. carinatus from the Karksi outcrop in the Härma Member, the lowest unit of the Givetian Burtnieki Formation, showing that both spines and scales of D. crassisimus occur in the Givetian of the eastern Baltic.…”
Section: Discussionmentioning
confidence: 81%
“…As in Scotland (Figure 2.2), D. crassisimus has quite a long range in the eastern Baltic, also found in the Eifelian Narva Formation (Valiukevičius 1985(Valiukevičius , 2003. Märss et al (2008) also report D. carinatus from the Karksi outcrop in the Härma Member, the lowest unit of the Givetian Burtnieki Formation, showing that both spines and scales of D. crassisimus occur in the Givetian of the eastern Baltic.…”
Section: Discussionmentioning
confidence: 81%
“…Also, scales of the chondrichthyan elasmo− branch? Seretolepis elegans Obruchev and Karatajãt− Talimaa 1968), Knerialepis mashkovae (Karatajãt− Talimaa, 1997), Altholepis composite Karatajãt−Tali− maa, 1997 and Ivanelepis costulata Karatajãt− Talimaa, 1997(Karatajãt−Talimaa 1997Hanke and Kara− tajãt−Talimaa 2002;Märss et al 2008) were found in limestone beds of the Chortkiv Stage. The number of recognised acanthodian forms reached 17, including all species from the preceding Stage (Valiukevičius 2000) as well.…”
Section: Marine Devonian Stratamentioning
confidence: 99%
“…In earlier works Pärnu and Gauja deposits are considered as tide-influenced delta sediments (Ponten & Plink-Björklund 2007;Tovmasyan et al 2008). However, the grain morphology and lithological character of sections (Märss et al 2008) show that delta deposition alternated with beach conditions and breaks in sedimentation. In the studied sections levels with smoothed and rounded grains alternate with levels dominated by subangular particles.…”
Section: Discussionmentioning
confidence: 95%